2006
DOI: 10.1002/art.21651
|View full text |Cite
|
Sign up to set email alerts
|

Higher chondrogenic potential of fibrous synovium– and adipose synovium–derived cells compared with subcutaneous fat–derived cells: Distinguishing properties of mesenchymal stem cells in humans

Abstract: Objective. Mesenchymal stem cells from synovium have a greater proliferation and chondrogenic potential than do those from bone marrow, periosteum, fat, and muscle. This study was undertaken to compare fibrous synovium and adipose synovium (components of the synovium with subsynovium) to determine which is a more suitable source for mesenchymal stem cells, especially for cartilage regeneration, and to examine the features of adipose synovium-derived cells, fibrous synovium-derived cells, and subcutaneous fat-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
267
3
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 278 publications
(290 citation statements)
references
References 45 publications
14
267
3
6
Order By: Relevance
“…Some suggest a decrease in differentiation capacity with age or osteoarthritis, 13,43,44 whereas others suggest no such relation. 35,45,46 Therefore, our findings may not relate to MSCs from young healthy donors. However, our result can offer clues for further development of practical protocols for the clinical application of synovium-derived MSCs in osteoarthritic patients.…”
Section: Discussionmentioning
confidence: 84%
“…Some suggest a decrease in differentiation capacity with age or osteoarthritis, 13,43,44 whereas others suggest no such relation. 35,45,46 Therefore, our findings may not relate to MSCs from young healthy donors. However, our result can offer clues for further development of practical protocols for the clinical application of synovium-derived MSCs in osteoarthritic patients.…”
Section: Discussionmentioning
confidence: 84%
“…The two MSCs contain common features, but distinguishing properties dependent on their origin are emerging. [6][7][8][9]11,12 Colony-forming efficiency was higher in synovium-MSCs but colony size was larger in bone marrow-MSCs. 7 Expression of PDGF receptor-a was higher in synovium-MSCs based on flow cytometrical analysis.…”
Section: Morphology During Chondrogenesis Of Mscsmentioning
confidence: 99%
“…[6][7][8] MSCs derived from various mesenchymal tissues contain common features, but distinguishing properties due to their origin are emerging. [9][10][11][12] However, morphological differences of MSCs dependent on the source, especially during chondrogenesis, remain unknown.…”
mentioning
confidence: 99%
“…MSCs derived from non-cartilaginous knee joint tissues such as the infrapatellar fat pad (IFP) (Dragoo et al 2003;English et al 2007;Jurgens et al 2009;Buckley et al 2010a; Buckley et al 2010b) and synovium (Sakaguchi et al 2005;Yokoyama et al 2005; Mochizuki et al 2006;Pei et al 2008;Pei et al 2009;Sampat et al 2011) have been shown to possess significant chondrogenic potential. One of the key challenges in cartilage tissue engineering is ensuring sufficient functionality of the construct to be implanted which is capable of withstanding the challenging mechanical environment of the joint.…”
Section: Introductionmentioning
confidence: 99%